2019
DOI: 10.1002/pmic.201900174
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Proteome Signatures Associated with Five Grades of Prostate Cancer and Benign Prostatic Hyperplasia

Abstract: The histology‐based Gleason score (GS) of prostate cancer (PCa) tissue biopsy is the most accurate predictor of disease aggressiveness and an important measure to guide treatment strategies and patient management. The variability associated with PCa tumor sampling and the subjective determination of the GS are challenges that limit accurate diagnostication and prognostication. Thus, novel molecular signatures are needed to distinguish between indolent and aggressive forms of PCa for better patient management a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 53 publications
1
31
0
Order By: Relevance
“…Quantitative proteomics studies comparing primary tumors to benign tissue ( Table 1 ) describe a number of DEPs which have been identified between PCa and non-malignant tissue from the same patient [ 59 ], PCa and benign prostatic hyperplasia (BPH) [ 50 , 53 , 56 ], low-risk and high-risk prostate cancer groups [ 46 ], low- and high-grade prostate cancer [ 51 ], different ISUP grades [ 50 ], and even laser-capture microdissection (LCM)-isolated cellular fractions, such as epithelial cells of different Gleason grade [ 48 ] or ERG status [ 60 ]. Although many of these studies find alterations in expression levels of several proteins previously well-known to be aberrantly expressed in prostate cancer, significant heterogeneity exists in the identity of the DEPs identified.…”
Section: Proteomes Of Clinical Prostate Cancer Samplesmentioning
confidence: 99%
“…Quantitative proteomics studies comparing primary tumors to benign tissue ( Table 1 ) describe a number of DEPs which have been identified between PCa and non-malignant tissue from the same patient [ 59 ], PCa and benign prostatic hyperplasia (BPH) [ 50 , 53 , 56 ], low-risk and high-risk prostate cancer groups [ 46 ], low- and high-grade prostate cancer [ 51 ], different ISUP grades [ 50 ], and even laser-capture microdissection (LCM)-isolated cellular fractions, such as epithelial cells of different Gleason grade [ 48 ] or ERG status [ 60 ]. Although many of these studies find alterations in expression levels of several proteins previously well-known to be aberrantly expressed in prostate cancer, significant heterogeneity exists in the identity of the DEPs identified.…”
Section: Proteomes Of Clinical Prostate Cancer Samplesmentioning
confidence: 99%
“…The last hub gene is LMOD1, also known as Leiomodin-1, could be activated by serum response factor (SRF) or myocardin (MYOCD) and functions in smooth muscle cell differentiation [39]. Previous studies reported that aberrant upregulation of LMOD1 as a poor prognostic marker in a variety of tumors, including colorectal cancer, Leiomyosarcoma and prostate cancer [40][41][42]. The relationship between LMOD1 and the pathogenesis of BCa remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the risk-associated genes, APOBEC3C was discovered as a vital member of the APOBEC family that encodes the APOBEC3C (apolipoprotein B mRNA editing enzyme catalytic subunit 3C, or A3C), clustered in the human chromosome 22 (Jarmuz et al, 2002). Some investigations have shown that the expression of APOBEC3C played a positive role in the invasiveness and prognosis of breast cancer (Zhang et al, 2015;Wang et al, 2019), hepatocellular carcinoma (Yang et al, 2015), and prostate cancer (Kawahara et al, 2019). Taking into account investigations on the role of GNG5 in carcinogenesis, Orchel et al (2012) found that GNG5 may play a vital role in pathogenesis or progression of endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%